2012
DOI: 10.1002/qj.2079
|View full text |Cite
|
Sign up to set email alerts
|

Snowbands over the English Channel and Irish Sea during cold‐air outbreaks

Abstract: Persistent northerly-to-easterly cold-air outbreaks affected the UK during the winters of 2009-10 and 2010-11, with the resulting convection frequently organizing into snowbands over the English Channel and Irish Sea. Sounding data and composite radar reflectivity images from the Met Office Nimrod precipitation radar network reveal that these bands formed along the major axis of each body of water (or sea) when the boundary-layer flow was roughly parallel to each of those axes (along-channel). For both seas, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…At 0000 UTC on 2 February (Fig. 4a), the easterly winds had Â12 m s , and similar to those found by other authors (Andersson and Nilsson, 1990;Norris et al, 2012). Finally, considering the Gulf of Finland as a lake, the morphology of the observed and simulated snow band at this time is quite similar to Type I, which is described by Niziol et al (1995).…”
Section: Simulation Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…At 0000 UTC on 2 February (Fig. 4a), the easterly winds had Â12 m s , and similar to those found by other authors (Andersson and Nilsson, 1990;Norris et al, 2012). Finally, considering the Gulf of Finland as a lake, the morphology of the observed and simulated snow band at this time is quite similar to Type I, which is described by Niziol et al (1995).…”
Section: Simulation Resultssupporting
confidence: 88%
“…(1 km across the long axis of the gulf, as other authors found in other snow-band events (Laird et al, 2003a;Norris et al, 2012;Savija¨rvi, 2012). During the second part of these events, a southerly wind regime (wind across coasts) prevailed, and the observed and simulated coastal line of precipitation moved inland to the downwind (Finnish) coast.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Snowbands have been observed in association with mesoscale gravity waves (e.g., Bosart et al 1998;Koch and Siedlarz 1999). Lake-effect and sea-effect snowbands (e.g., Passarelli and Braham 1981;Niziol et al 1995;Norris et al 2013) can form in the boundary layer associated with horizontal convective rolls, even over land (e.g., Schultz et al 2004). Bands have also been attributed to the release of moist symmetric instability (e.g., Seltzer et al 1985;Wolfsberg et al 1986) or the release of conditional, dry symmetric, and inertial instabilities (e.g., Jascourt et al 1988;Knox and Hoggatt 1996;Hoggatt and Knox 1998;Schultz and Knox 2007).…”
Section: Introductionmentioning
confidence: 99%